2022
DOI: 10.3389/fimmu.2022.933468
|View full text |Cite
|
Sign up to set email alerts
|

Role of B-Cell in the Pathogenesis of Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is a rare multisystem autoimmune disease, characterized by fibrosis, vasculopathy, and autoimmunity. Recent advances have highlighted the significant implications of B-cells in SSc. B-cells are present in affected organs, their subpopulations are disrupted, and they display an activated phenotype, and the regulatory capacities of B-cells are impaired, as illustrated by the decrease in the IL-10+ producing B-cell subpopulation or the inhibitory membrane co-receptor density. Recent multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 132 publications
1
14
0
Order By: Relevance
“…Therefore, IL-10 can regulate the TLR4/NF-κB pathway in dermal fibroblasts through the IL-10 receptor (IL-10R)/STAT3 axis to reduce both ECM protein deposition and fibroblast transformation to myofibroblasts, thereby inhibiting the formation of skin scar induced by lipopolysaccharide. In addition, Thoreau et al ( 71 ) found that the expression of IL-10 was reduced in mouse models and patients with SSc and was associated with ILD formation. We found that the expression of COL1A1 in SSc plasma cirexos was negatively correlated with IL-10 in the SSc serum, which is consistent with the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL-10 can regulate the TLR4/NF-κB pathway in dermal fibroblasts through the IL-10 receptor (IL-10R)/STAT3 axis to reduce both ECM protein deposition and fibroblast transformation to myofibroblasts, thereby inhibiting the formation of skin scar induced by lipopolysaccharide. In addition, Thoreau et al ( 71 ) found that the expression of IL-10 was reduced in mouse models and patients with SSc and was associated with ILD formation. We found that the expression of COL1A1 in SSc plasma cirexos was negatively correlated with IL-10 in the SSc serum, which is consistent with the abovementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these immune cells further contribute to the inflammatory and fibrotic processes associated with SSc. Targeting B cells and their activity has become a therapeutic approach in SSc [7–9]. For example, rituximab, a monoclonal antibody that selectively depletes B cells, has been used in SSc patients with promising results [10,11,12 ▪ ,13–18].…”
Section: Introductionmentioning
confidence: 99%
“…A possible drawback for RTX efficacy may come from the fact that this drug is certainly efficacious in B cell depletion but plasma cells and hematopoietic stem cells are not among its targets. Long-lived plasma cells are thought to be an important player in SSc pathogenesis, as they infiltrate the skin of SSc patients together with CD20+ B cells and being the main source of SSc autoantibodies, that may also have a functional role ( 9 ).…”
Section: Introductionmentioning
confidence: 99%